2023
DOI: 10.1002/adhm.202302597
|View full text |Cite
|
Sign up to set email alerts
|

Reversing Resistance of Cancer Stem Cells and Enhancing Photodynamic Therapy Based on Hyaluronic Acid Nanomicelles for Preventing Cancer Recurrence and Metastasis

Teng Wang,
Jiaojiao Tao,
Bingjie Wang
et al.

Abstract: Photodynamic therapy (PDT) is a promising approach for tumor treatment; however, the therapeutic resistance of cancer stem cells (CSCs) severely limits its efficacy and easily lead to recurrence. Herein, a hyaluronic acid (HA)‐Ce6‐Olaparib (OLA) micelle (HCCO) is developed, which combines the CSC targeting of HA, the PDT effect of Ce6, and the DNA damage repair inhibition of OLA. More importantly, HCCO induces immunogenic cell death (ICD) effects, promotes dendritic cells maturation, and alleviates myeloid‐der… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Moreover, PDT in combination with DNA repair inhibitors seems to be a promising strategy to overcome drug resistance. It has been recently reported that the combination of chlorin e6 and a DNA repair inhibitor (Olaparib) successfully prevented tumor recurrence and metastasis in vivo for 4T1 breast cancer [31].…”
Section: Increased Dna Damage Repairmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, PDT in combination with DNA repair inhibitors seems to be a promising strategy to overcome drug resistance. It has been recently reported that the combination of chlorin e6 and a DNA repair inhibitor (Olaparib) successfully prevented tumor recurrence and metastasis in vivo for 4T1 breast cancer [31].…”
Section: Increased Dna Damage Repairmentioning
confidence: 99%
“…CSCs play a significant role in tumor initiation, sustaining its growth and survival. They can also inhibit the immune response by preventing the maturation of dendritic cells [31]. Moreover, they are believed to exhibit greater resistance and possess different metabolic, genetic, and epigenetic signatures compared to non-CSCs, posing an additional challenge to overcoming resistance.…”
Section: Cancer Stem Cellsmentioning
confidence: 99%
See 1 more Smart Citation